TEOLOGI ASY’ARIYAH: SEJARAH DAN PEMIKIRANNYA - Yogi Sulaeman; Zinul Almisri; Kerwanto (LPPM STAI Nida El-Adabi, 2023)
Asy'ariyah is a theology founded by Abu Hasan Al-Asy'ari. This theology is often referred to as